2021
DOI: 10.21203/rs.3.rs-634309/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-free Functional and Structural Imaging of Liver Microvascular Complex in Mice by Jones Matrix Optical Coherence Tomography

Abstract: We demonstrate label-free imaging of the functional and structural properties of microvascular complex in mice liver. The imaging was performed by a custom-built Jones-matrix based polarization sensitive optical coherence tomography (JM-OCT), which is capable of measuring tissue’s attenuation coefficient, birefringence, and tiny tissue dynamics. Two longitudinal studies comprising a healthy liver and an early fibrotic liver model were performed. In the healthy liver, we observed distinctive high dynamics benea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…The sections were imaged under a microscope (BZ-X710, Keyence Corp., Osaka, Japan) with an 10× objective (NA = 0.3). was found in our previous study [39] and are known to be blood vessels. A tessellated texture appears in the slab projection of OCT [Fig.…”
Section: Histologysupporting
confidence: 65%
See 2 more Smart Citations
“…The sections were imaged under a microscope (BZ-X710, Keyence Corp., Osaka, Japan) with an 10× objective (NA = 0.3). was found in our previous study [39] and are known to be blood vessels. A tessellated texture appears in the slab projection of OCT [Fig.…”
Section: Histologysupporting
confidence: 65%
“…Although vascular structure was not clear in the OCT intensity in this study [Fig. 1(b) and (c)], our previous study of normal mouse liver suggests that the high-LIV locates just beneath the vascular lumen [39]. Accordingly, the high-LIV vessel-like structures in this study also colocate with the tissue beneath or around vessels.…”
Section: Vessel-like Structures In the Normal-diet Liver: Periportal ...contrasting
confidence: 54%
See 1 more Smart Citation
“…Several DOCT methods have been demonstrated to visualize the magnitude [28,29], frequency [30][31][32], and time-correlation [28,33,34] of the intratissue and intracellular activities. DOCT has been applied to a variety of samples including human esophageal and cervical biopsies [32], ex vivo mouse or rat organs [29][30][31][34][35][36], in vivo zebrafish [37], in vitro cell culture [38], spheroid [28,39], mammaria organoid [40], and retinal organoid [41]. Among the DOCT techniques, logarithmic-intensity-variance (LIV) contrasts the fluctuation magnitude of the OCT signal intensity [28], and is expected to be sensitive to the magnitude of intratissue and intracellular motility.…”
Section: Introductionmentioning
confidence: 99%
“…Among the DOCT techniques, logarithmic-intensity-variance (LIV) contrasts the fluctuation magnitude of the OCT signal intensity [28], and is expected to be sensitive to the magnitude of intratissue and intracellular motility. In previous studies, LIV has revealed the functional structures of ex vivo mouse organs [35,36] and in vitro tumor spheroids [28,39].…”
Section: Introductionmentioning
confidence: 99%